High efficiency electron-blocking-layer-free deep ultraviolet LEDs with graded Al-content AlGaN insertion layer. (October 2021) - Shi, Lang; Du, Peng; Tao, Guoyi; Liu, Zongyuan; Luo, Wei; Liu, Sheng; Zhou, Shengjun
Abstract: AlGaN-based deep ultraviolet light-emitting diodes (DUV-LEDs) generally employ an electron blocking layer (EBL) to suppress electron leakage. However, the EBL can also hinder holes from injecting into active region, resulting in that internal quantum efficiency (IQE) of conventional DUV-LED with EBL can be compromised. Here we propose an electron-blocking-layer-free DUV-LED where graded Al-content AlGaN layer is inserted into quantum barrier (QB) to enhance electron blocking ability. Carrier transport in the proposed DUV-LED structure is investigated numerically. The simulation results show that the graded Al-content AlGaN insertion layer can effectively suppress electron leakage and enhance hole injection efficiency, resulting in an improvement in radiative recombination rate. As a result, the maximum IQE for the proposed AlGaN-based DUV-LED structure is 86.9%, greatly increased by 64.3% compared to the conventional DUV-LED with EBL. Additionally, the efficiency droop of DUV-LED with graded Al-content AlGaN insertion layer is remarkably reduced from 18.9% to 3.4% at 200 mA. Highlights: Graded Al-content AlGaN layer is inserted into quantum barrier of electron-blocking-layer-free AlGaN-based deep ultraviolet Light-emitting diode.